ISSUES OF OPTIMIZATION OF METHOTREXATE THERAPY IN PATIENTS WITH RHEUMATOID ARTHRITIS - G. I. Gridneva; Yu. V. Muravyev; E. L. Luchikhina; N. V. Demidova; D. E. Karateev (Научно-практическая ревматология, 2017)
Objective: to evaluate the safety and efficiency of monotherapy with methotrexate (MTX) solution for subcutaneous injection (SC MTX), by using the estimated dosing, in patients with rheumatoid arthritis (RA).Subjects and methods. A 12-month prospective controlled study enrolled 106 patients with early RA who were given SC MTX was conducted at the V.A. Nasonova Research Institute of Rheumatology in the framework of the REMARCA (Russian invEstigation of MethotrexAte and biologicals for eaRly aCtive Arthritis) program.Results and discussion. 12-month SC MTX monotherapy could achieve the treatment goal (remission or low disease activity) in 68% of the patients with active RA who did not need biological agents (BAs). In 36% of the patients, the treatment caused adverse reactions (ARs) that were the basis for its complete discontinuation in 8%. The therapeutic effect of SC MTX depended on body mass index (BMI) and was more pronounced in patients with its normal values (≤25 kg/m2) than in those with overweight or obesity. The incidence of ARs did not depend on the duration of the disease and the weight of a patient receiving SC MTX. Addition of BAs to SC MTX monotherapy did not lead to an increase in the frequency of ARs. In early RA, the effect was better when SC MTX was used in combination with lowdose oral glucocorticoids. The findings showed the expediency of intensively using SC MTX at the doses calculated per 1 m2 of the body surface, the dependence of therapeutic action and the independence of the frequency and severity of ARs from the patient’s BMI.